2009
DOI: 10.1159/000235553
|View full text |Cite
|
Sign up to set email alerts
|

Skin Efficacy and Biophysical Assessment of Glycerol-Containing Hydrocolloid Patches

Abstract: Hydrocolloid patches are developed with 10, 20 and 30% (w/w) glycerol as the main active ingredient. By making use of two experimental forearm models, skin efficacy and its dependency on the glycerol concentration applied were compared with a blank reference patch, a commercialized protective patch and a cosmetic barrier cream. Skin hydration and transepidermal water loss measurements were combined with skin erythema assessments. After a single application to healthy skin, a clear concentration-dependent effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The penetration is therefore increased compared to the nanosuspension without additives. The penetration enhancement is concentration dependent, because the increase of the concentration of glycerol, i.e., from 2% to 5%, increased the skin moisturizing properties [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The penetration is therefore increased compared to the nanosuspension without additives. The penetration enhancement is concentration dependent, because the increase of the concentration of glycerol, i.e., from 2% to 5%, increased the skin moisturizing properties [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…They all increased skin hydration to the same extent. This was expected as 5% (w/w) of glycerol - well known for its stratum corneum humectancy - was added to the basic W/O formula in which the different silicones were incorporated [7,29,47,48]. …”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies have demonstrated that topical moisturizer alone improves psoriasis . Previous studies have shown that both Cer and glycerol, ingredients in our moisturizer, increase SC hydration in normal and diseased skin . In addition, the activation of PPARγ by LA upregulates aquaporin 3 expression , which in turn increases skin hydration .…”
Section: Discussionmentioning
confidence: 96%